Point Cumana, Trinidad - (:unkn) unknown (Muir, Marshall and Co., Port of Spain, Trinidad., 2009)
A picture of a man sitting on a bench at the side of a dirt path with his back to the calm waters of the Gulf of Paria.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Point Cumana; Coasts--Trinidad and Tobago; Men--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Benches--Trinidad and Tobago; Seashore--Trinidad and Tobago; Paria, Gulf of (Venezuela and Trinidad and Tobago); [1930]; Trails--Trinidad and Tobago; Roads--Trinidad and Tobago